2020
DOI: 10.3390/catal10111276
|View full text |Cite
|
Sign up to set email alerts
|

A Discussion on the Unique Features of Electrochemical Promotion of Catalysis (EPOC): Are We in the Right Path Towards Commercial Implementation?

Abstract: The phenomenon of “Non-Faradaic Electrochemical Modification of Catalytic Activity (NEMCA)” or “Electrochemical Promotion of Catalysis (EPOC)” has been extensively studied for the last decades. Its main strength, with respect to conventionally promoted catalytic systems, is its capability to modify in-situ the activity and/or selectivity of a catalyst by controlling the supply and removal of promoters upon electrical polarization. Previous reviews have summarized the main achievements in this field from both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…21,33,[35][36][37] In contrast to the traditionally used organometallic pastes, the main advantage of free-standing NPs includes the uniform metal dispersion on the solid electrolyte as well as thin and highly porous catalytic films. 26 In this regard, the used sample was characterized through scanning electron microscopy (SEM). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,33,[35][36][37] In contrast to the traditionally used organometallic pastes, the main advantage of free-standing NPs includes the uniform metal dispersion on the solid electrolyte as well as thin and highly porous catalytic films. 26 In this regard, the used sample was characterized through scanning electron microscopy (SEM). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21 More specifically, the EPOC effect, also known as non-faradaic electrochemical modification of catalytic activity (NEMCA) is a highly utilized tool in heterogeneous catalysis over the past 40 years. [22][23][24][25][26][27] This effect is commonly studied with a simple and straightforward experimental set up involving three metal electrodes deposited onto a solid electrolyte/ion conductor as shown in Fig. S1.…”
Section: Introductionmentioning
confidence: 99%
“…SR of methanol can be the most relevant case to ethanol reforming as both feedstocks categorized as primary alcohols, and the studied catalytic systems were Ni and Cu both supported on KβAl2O3 [38,39]. Most of these studies have shown the interest of EPOC in the H2 production technology 4 as reviewed in recent publications [44,45]. Nonetheless, the commercial implantation of the EPOC phenomenon has not been developed yet, being the poorly dispersed materials on the electrode, the reactor configuration or the study of the adequate processes the main drawbacks [45].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have shown the interest of EPOC in the H2 production technology 4 as reviewed in recent publications [44,45]. Nonetheless, the commercial implantation of the EPOC phenomenon has not been developed yet, being the poorly dispersed materials on the electrode, the reactor configuration or the study of the adequate processes the main drawbacks [45].…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13 This process has been shown to increase the EO selectivity with relatively small (μA/cm 2 to mA/cm 2 ) applied currents. 3,14,15 Previous studies have examined the effect of varying current density on selectivity at different applied currents and demonstrate that a higher applied current increases selectivity and total catalytic rate. 16 The proper molar ratio of ethylene to oxygen in the feed gas is not well agreed upon, with studies finding evidence that both ethylene-rich and oxygen-rich feeds produce a higher selectivity.…”
mentioning
confidence: 99%